Development of a prototype semi-automatic bicycle hanger - Azhar, Aiman Asyra (2024)
This project aims to address the limitations of manual bicycle hangers by developing an innovative automatic bicycle hanger system. The objective is to design and fabricate a secure and stable product within a budget of RM 300, which enhances the ease and security of bicycle storage. The existing manual hangers lack flexibility in accommodating different bicycle sizes and weights, pose a risk of damage to the bicycle, and make the storage process physically demanding. By utilizing motorized components and advanced design principles, the automatic hanger system will provide a user-friendly solution, specifically targeting bicycle owners facing challenges in crowded spaces. The project will employ a design-based approach, encompassing research, conceptualization, prototyping, and testing. The expected result is a functional automatic bicycle hanger system that improves storage efficiency, accommodating standard-sized bicycles, and enhances convenience and security in bicycle storage, contributing to a practical and affordable solution for bicycle owners